Cooperative Collision Avoidance for the Voyager Unmanned Ground Vehicle: Practical Implementation and Demonstration - Mtimkulu, Thando (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.